The Early Ayn Rand a Selection from Her Unpublished Fiction - Rand, Ayn 1905-1982 (Penguin, 2005)
Includes a selection of early short stories, excerpts from "The Fountainhead," and two full-length plays, with a critical introduction to the writer as an artist and philosopher. Reissue
Keywords: Anthologie